2011
DOI: 10.1093/nar/gkr488
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced translation by Nucleolin via G-rich elements in coding and non-coding regions of target mRNAs

Abstract: RNA-binding proteins (RBPs) regulate gene expression at many post-transcriptional levels, including mRNA stability and translation. The RBP nucleolin, with four RNA-recognition motifs, has been implicated in cell proliferation, carcinogenesis and viral infection. However, the subset of nucleolin target mRNAs and the influence of nucleolin on their expression had not been studied at a transcriptome-wide level. Here, we globally identified nucleolin target transcripts, many of which encoded cell growth- and canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(142 citation statements)
references
References 68 publications
5
136
1
Order By: Relevance
“…Cell surface nucleolin is even proved to be a specific marker of angiogenic endothelial cells in the vasculature 39. Moreover, nucleolin displayed remarkably cardioprotective, antiapoptotic and tumour inhibitory effects, etc 18, 23, 40, 41. In the present study, we found that HSYA dominantly increased the nucleolin expression in the ischaemic myocardium and HUVECs.…”
Section: Discussionsupporting
confidence: 54%
“…Cell surface nucleolin is even proved to be a specific marker of angiogenic endothelial cells in the vasculature 39. Moreover, nucleolin displayed remarkably cardioprotective, antiapoptotic and tumour inhibitory effects, etc 18, 23, 40, 41. In the present study, we found that HSYA dominantly increased the nucleolin expression in the ischaemic myocardium and HUVECs.…”
Section: Discussionsupporting
confidence: 54%
“…29 Several RNA-binding proteins (HuR, nuclear factor 90, tristetraprolin, butyrate response factor 1, and K homology-type splicing regulatory protein) preferentially interact with U/AU-rich sequences in the 3′ UTR of the target transcripts and regulate their stability, whereas nucleolin preferentially binds to G-rich sequences. 30 SR proteins also participate in the regulation of mRNA turnover. For example, SRSF1 selectively enhances the decay of target mRNAs by binding to their 3′ UTRs.…”
Section: Discussionmentioning
confidence: 99%
“…Many of nucleolin target mRNAs bear AU-rich elements (AREs), typically present in their 3'-untranslated region (UTR), and/or G-rich sequences distributed in the 5' UTR, coding region (CR), and 3' UTR. 13,32 In this section, we will discuss those nucleolin target mRNAs which are best characterized, and we will highlight the impact of the encoded proteins in disease processes ( Table 1).…”
Section: Nucleolin Target Transcriptsmentioning
confidence: 99%
“…12 The central region of nucleolin contains four RNA-recognition motifs (RRMs) and mediates the interaction with mRNAs and pre-rRNA. 13,14 The C-terminal region of nucleolin contains an arginine/glycine-rich domain (RGG), through which nucleolin can interact with target mRNAs as well as with other proteins, including ribosomal proteins. 13,15,16 Nucleolin has been extensively implicated in DNA metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation